Epic Synthesis in Late Work of I. S. Turgenev - V. G. Andreeva (Научный диалог)
The epic synthesis in the works of I. S. Turgenev on the example of his last novel “Nov” is examined in the article. It is noted that the writer had high hopes for this work, since the novel was supposed to show Turgenev’s true position in relation to the Russian people and the future of Russia. It is pointed out that in “Nov” there is no extensively revealed theme of peasant life, but it does not recede into the background: Turgenev represents a collective image of the people, evaluates events from the people’s point of view. It is emphasized that the writer’s attention to the reaction of the public, conditioned by the desire not only to present the most complete picture of life in Russia, but also to show the reader timeless samples of meaningful life, rising above various “questions”, allows us to talk about the epic breadth of the novel. The author of the article proves that the artistic world of “Nov” can be read “layer by layer”, reaching the key meanings: behind the external clashes of political forces is the problem of the relationship between people, their willingness to help each other. Parallels are drawn between the three essays added to the book “Notes of a Hunter” and individual episodes of the novel “Nov”, their ideological and artistic connection is proved. It is concluded that the work of the late Turgenev cannot be analyzed without considering the opposition between the dramatic elements of destruction and the creative force, which is based on the Orthodox world outlook.